FEMINISME DAN KRITIK IDEOLOGI TERHADAP ILMU PENGETAHUAN - Nihayah, Ishmatun; Suharto, Yusuf (IAIN Kediri, 2020)
This study attempts to discuss feminism and ideological criticism of science. Feminism is a movement that fights for the rights of oppressed women as a result of injustice and inequality, both in terms of economics, social, politics, education and others. In Indonesia, it was spread by Raden Ajeng Kartini, who fought for the women, especially in the field of education. Feminism movements in the world are various; liberal feminists,social feminism, radical feminism, Marxist feminism, ecofeminism, Islamic feminism and so on. These feminisms are different in analyzing the causes of injustice and the goals and forms of their struggle. Although having different opinions, they contain the same core struggle, i.e awareness of injustice against women in the family or community. This study focuses on feminism and ideological criticism of science. In the past time, men andwomen did not get the same education rights. Women could only get low education and only work indoors, while men received high education and obtained jobs as they wanted. Thus, men have a broader knowledge of science, they could create sophisticated technology to ease their burden.Keywords: Feminism, Ideology Criticism, Science